Utilização de gonadotropina coriônica equina em protocolos de inseminação artificial em tempo fixo em bovinos de corte - Mercadante, Vítor Rodrigues Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Current cattlemen must seek methods to maximum reproductive efficiency of their beef herds, making the business competitive and enhancing greater profitability. For the cow-calf producers, efficiency translates into more cows producing one calf every year. Fixed-time artificial insemination (TAI) is one of several technologies that producers utilize to reach this goal. Postpartum anestrus is one of the biggest obstacles to overcome in order to obtain suitable results at the end of the breeding season. The TAI protocols are efficient in re-establishing cyclicity in noncycling cows during the postpartum period, streamlining the use of labor on farms, allowing the use of artificial insemination (AI) on a large scale, and introducing superior genetics to the herd. The protocols that are most commonly used in Brazil are based on progesterone (P4) releasing devices that prevent premature estrus and ovulation; and estradiol (E2) to synchronize the initiation of a new follicular wave. In such protocols, administration of equine chorionic gonadotropin (eCG) helps the development of the follicle, increases ovulation rate, improves the endocrine and uterine environment during proestrus and diestrus, and improves fertility. The use of eCG in TAI protocols for suckled cows, non-lactating cows and heifers increases the pregnancy rate allowing more calves at the end of the breeding season and higher profitability to the cattlemen

O pecuarista atual deve buscar sempre a máxima eficiência produtiva de seu rebanho, tornando sua empresa rural competitiva e alcançando maior lucratividade. Para o setor de cria, eficiência se traduz em obter um bom bezerro por matriz por ano. Diversas tecnologias buscam auxiliar o pecuarista nessa tarefa. A inseminação artificial em tempo fixo (IATF) é uma delas. Os protocolos de IATF são eficientes em retirar as fêmeas do anestro pós-parto, grande entrave para os bons resultados reprodutivos ao final da estação de monta, racionalizam o uso da mão-de-obra na fazenda e possibilitam o uso da inseminação artificial (IA) em larga escala, introduzindo genética superior ao rebanho. Os protocolos mais utilizados no Brasil têm como base implantes de progesterona (P4) e estradiol (E2) para sincronizar a onda de crescimento folicular. Nesses protocolos, a administração de gonadotropina coriônica equina (eCG) auxilia o melhor desenvolvimento do folículo, aumenta a taxa de ovulação e melhora o ambiente endócrino e uterino durante o proestro e diestro, incrementando a fertilidade. O uso de eCG em protocolos de IATF para vacas paridas, solteiras e novilhas aumenta a taxa de prenhez, gerando mais bezerros no final da estação de monta e maior lucratividade ao produtor
Keywords: Bovino - Reprodução; Bovino - Inseminação artificial; Prenhez de novilhas; Bovino de corte; Protocolos de IATF; eCG